Rancang bangun smart nose pendeteksi zat pengawet berbahaya pada ikan - Hervina Puspita Darmayanti; Nurhikmah Fitriani; Diah Setiani; Siti Nurfadilah; Irnin Agustina Dwi Astuti (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2021)
Fish is a source of protein that is widely consumed by indonesians, easy to obtain, and cheap. This foodstuff, quickly undergoes a process of decay caused by the growth of microorganisms, fish producers often use preservatives so that this product is not quickly damaged, especially preservatives that are not allowed formaldehyde. Therefore, a tool is needed that can easily detect the content of formaldehyde. We make a tool called smart nose that is a detection of harmful preservatives in fish. This research aims to create a smart nose tool design that can detect the content of formaldehyde in fish. The tools and materials used to assemble the components are the Arduino, jumper cable, HCHO sensor, LED, resistor, LCD and Bluetooth HC-05 module, as well as arduino IDE software to program the circuit. After the components are assembled, a smart nose tool is obtained that can detect the content of formaldehyde in PPM units.